A Versatile CuII Metal–Organic Framework Exhibiting High Gas Storage Capacity with Selectivity for CO2: Conversion of CO2 to Cyclic Carbonate and Other Catalytic Abilities. Issue 10 (2nd February 2016) - De, Dinesh; Pal, Tapan K.; Neogi, Subhadip; Senthilkumar, S.; Das, Debasree; Gupta, Sayam Sen; Bharadwaj, Parimal K.
Abstract: A linear tetracarboxylic acid ligand, H4 L, with a pendent amine moiety solvothermally forms two isostructural metal–organic frameworks (MOFs)LM (M=Zn II, Cu II ). FrameworkLCu can also be obtained fromLZn by post‐ synthetic metathesis without losing crystallinity. Compared withLZn, theLCu framework exhibits high thermal stability and allows removal of guest solvent and metal‐bound water molecules to afford the highly porous, LCu ′ . At 77 K, LCu ′ absorbs 2.57 wt % of H2 at 1 bar, which increases significantly to 4.67 wt % at 36 bar. The framework absorbs substantially high amounts of methane (238.38 cm 3 g −1, 17.03 wt %) at 303 K and 60 bar. The CH4 absorption at 303 K gives a total volumetric capacity of 166 cm 3 (STP) cm −3 at 35 bar (223.25 cm 3 g −1, 15.95 wt %). Interestingly, the NH2 groups in the linker, which decorate the channel surface, allow a remarkable 39.0 wt % of CO2 to be absorbed at 1 bar and 273 K, which comes within the dominion of the most famous MOFs for CO2 absorption. Also, LCu ′ shows pronounced selectivity for CO2 absorption over CH4, N2, and H2 at 273 K. The absorbed CO2 can be converted to value‐added cyclic carbonates under relatively mild reaction conditions (20 bar, 120 °C). Finally, LCu ′ is found to be an excellent heterogeneous catalyst in regioselective 1, 3‐dipolar cycloaddition reactions ("click" reactions) and provides an efficient, economic route for the one‐pot synthesis of structurally divergent propargylamines through three‐component coupling of alkynes, amines, and aldehydes. Abstract : Storage and conversion combined : A novel NbO‐type metal–organic frameworkLCu with pores decorated with NH2 groups exhibits notably high and selective storage of CO2 and its conversion to cyclic carbonate (see figure). Additionally, it can catalyze 1, 3‐dipolar cycloadditions as well as A 3 ‐coupling reactions.